Relationship Between Disease History and Fear Level During COVID-19 Pandemic in Bogor City Area - Devi Irawan; Nining Fitrianingsih; Magdalena A. Yosali; Widia Astuti AW; Yufi Aliyupiudin; Joshua Francisco (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: COVID-19 pandemic is a major concern in almost all countries in the world, including in Indonesia.The number of COVID-19 confirmed cases in the worldwide as of July 20, 2021 was 192 million cases with4.13 million deaths. West Java province of Indonesia became one of the highest COVID-19 contributors with 6,928cases in one day. This very rapid increase has caused psychological impact in society. Some people became moreafraid to get infected with COVID-19 while some others started to get careless in performing health protocols.COVID-19 imposes more threat to people with previous diseases and could also raise fear and anxiety during theoutbreak.Objective: The purpose of this study was to determine the relationship between disease history and fear level ofCOVID-19 in Bogor City area.Methodology: The research method used was analytical survey with a cross-sectional approach. The samplingtechnique was snowball sampling with total of 515 participants aged more than 18 years old. The instrument inthe study was an online questionnaire using a Google Form. Data analysis performed was univariate and bivariateanalysis with chi square test.Result: Out of 515 participants, 431 respondents (83.7%) had no disease history and 411 respondents (79.8%) hadmoderate fear level of COVID-19. The results of the chi square test show the p-value = 0.000.Conclusion: There was a relationship between disease history and fear level of COVID-19 in in Bogor City area.